Being Old in Dalit Community: A Study from Bajhang Nepal (KMC Journal, 2023)
Dalit is a name for people belonging to the lowest stratum castes in Nepal and India, previously characterized as untouchable but now this discrimination is illegal. This study examines the socio-economic and health status of older Dalits living in the Jaya Prithvi Municipality of Bajhang district, Nepal. The source of data for this study is based on the 381 primary data collected from the face-to-face field survey carried out in 2021. This study found more than half of respondents were residing with their son/daughter-in-law (53.2%). Elderly living with a spouse only was quite high (37.4%) than in other studies from Nepal. It shows the emerging trend of living arrangements slightly different than previous other studies of the Nepalese elderly. Out of the total respondents, nearly 95 percent have at least one health problem. More than 90 percent of respondents have feelings of loneliness (92.1%) and depression (94.7%). Further, more than half of the respondents (59.4%) feel that they are not cared for by their family members and nearly two-thirds (65.7%) have feelings of insecurity. Local governments and stakeholders, including public health officials, should start health promotion programmes and awareness activities focusing on Dalits older people so that older people can live dignified lives in their later years.